Anaesthetic responses and reflexes to propofol and its combination in swine - RANA, MD. SOHEL; RAHMAN, MD. MIZANUR; JUYENA, NASRIN SULTANA (The Indian Journal of Animal Sciences, 2018)
To determine the effectiveness of propofol alone (P), and the combination of xylazine-propofol (XP), xylazineketamine (XK), xylazine-thiopentone (XT), anaesthetic protocols were studied in randomly selected 16 healthy indigenous pigs of either sexes, age 12 to 15 months and weight ranging from 12 to 16 kg. The responses of propofol and the combinations in different stages of anaesthesia were closely monitored. Various reflex responses and muscle tenacity were also observed concurrently during the period of anaesthesia. The study found the shortest (0.29±0.02 min) induction period with XT anaesthesia and the longest (2.95±0.21 min) by XK; whereas, induction of anaesthesia with P and XP was 0.4±0.08 and 0.41±0.08 min respectively. The time required for maximum depth of anaesthesia was the shortest in P (7.50±0.65 min) than the combinations. However, the anaesthetic protocol with XP produced the highest (65.25±3.30 min) duration of anaesthesia than the shortest (10.75±1.75 min) extent with P. Moreover, time to recovery from anaesthesia was higher (83.25±2.14 min) in XT and shorter (18.50±1.32 min) in P protocol. Good muscle relaxation was observed in XP, XK and XT combinations. Palpebral, conjunctival, jaw, tail and digital reflexes were almost absent in XP and XT combinations. The study concluded that propofol itself is a safe anaesthetic for short surgical interventions and its combination with xylazine is to be recommended for prolonged surgical procedures in swine.